Simulasi Pengaruh Excess Air terhadap Kinerja PLTU Kapasitas 12,5 MW pada Beban Bervariasi - Simanjuntak, Melvin Emil (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
The excess air is required to complete the combustion of fuel in the boiler. The amount of excess air differs from each power plant. It depends on the characteristic of the fuel such as the type and size of the fuel particle, the type of boiler and the type of combustion. Excess air that is too little will increase the unburnt fuel and while too much will reduce the power plantâ€™s performance. This study uses CycleTempo version 5.0 software to investigate the effect of excess air on the performance of a 12.5 MW steam power plant.Â The fuel used is low-rank coal. The lower heating value of 16960.15 kcal. The composition of coal used is Carbon 45.74%, Hydrogen 2.68%, Moisture 20%, Nitrogen 0.46%, Oxygen 14.94%, Sulphur 0.19% and Ash 15.99%. The load on the turbine was varied by 70%, 80%, 90% and 100% from its design capacity. The excess air used starts from 0% to 50%, where the interval 10%. This study finds that the optimum excess air is approximated at 20%. The excess air over 20% will increase boiler ratings, net heat rate, air and fuel consumption. In reverse will reduce boiler efficiency and thermal efficiency. The changes of excess air did not affect the heat removed by the condenser and the power used by the pump.